IDENTIFICATION OF AN ARBITRARY SHAPE RIGID OBSTACLE ILLUMINATED BY FLAT ACOUSTIC WAVE USING NEAR FIELD DATA - Tomasz Rymarczyk; Jan Sikora (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska)
The inverse problem concerning the identification of rigid surfaces of scattering objects formulated in the frequency domain is presented in this paper. Differences in the identification of concave objects, such as kite-shaped, and convex objects (circle) are indicated. The reader’s attention is focused on the conventional boundary element method with small number of boundary elements and the small number of sensors, which is significant for inverse problems.